Barriers to Export - Richard G. Harris (Queen's University, Department of Economics, 1990)
A model of entry by a small exporting country into a large country market with an incumbent monopolist is constructed, and export promotion policy is examined. In the presence of strategic entry deterrence by the large country incumbent firm a number of situations can emerge, including the possibility that, in the event of trade liberalization between countries, exports based on cost differences may fail to emerge, and a possibility that export promotion is world welfare improving. A model of multiple export markets with incomplete information on the part of the government is also considered. There it is shown that a policy of export promotion suffers from adverse selection (inefficient entry to export markets), but that this problem can be mitigated in the presence of incumbent monopolists in the potential export market who can actively deter entry.
Keywords: 411; 422; 423; 330; export subsidies; entry deterrence; economic integration